Child abuse and neglect: diagnostic and treatment guidelines - Shahla Prsa (Iran University of Medical Sciences, 1993)
Child abuse is a critical and extensive problem. Each year, in the United States, almost more than a million children are abused, and related injuries are accounted for 2,000 to 5,000 children deaths. Physicians are in an excellent and legal position to identify and report cases of child abuse and neglect. This guideline was provided to help general practitioners to identify and direct the different types of child abuse. A short historical preface and detailed information related to susceptible families, and children are presented.